2019
DOI: 10.1029/2018tc005340
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Foreland Structures on Hinterland Cooling: Evaluating the Drivers of Exhumation in the Eastern Bhutan Himalaya

Abstract: Understanding, and ideally quantifying, the relative roles of climatic and tectonic processes during orogenic exhumation is critical to resolving the dynamics of mountain building. However, vastly differing opinions regarding proposed drivers often complicate how thermochronometric ages are interpreted, particularly from the hinterland portions of thrust belts. Here we integrate three possible cross‐section geometries and kinematics along a transect through the eastern Bhutan Himalaya with a thermal model (Pec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 98 publications
(232 reference statements)
1
63
0
Order By: Relevance
“…(a) McQuarrie et al (2019) model a. (b) McQuarrie et al (2019) model b. (c) McQuarrie et al (2019) model c. Line of section by McQuarrie et al (2019) is indicated as B in Figure 1.…”
Section: Thermokinematic Modelingmentioning
confidence: 99%
See 4 more Smart Citations
“…(a) McQuarrie et al (2019) model a. (b) McQuarrie et al (2019) model b. (c) McQuarrie et al (2019) model c. Line of section by McQuarrie et al (2019) is indicated as B in Figure 1.…”
Section: Thermokinematic Modelingmentioning
confidence: 99%
“…The MCT mylonitic belt extends structurally downward for at least 3 km, as documented by pervasive ductile deformation of quartzites with progressive changes in dynamic recrystallization mechanisms (Grujic et al, 1996; Long, McQuarrie, Tobgay, & Hawthorne, 2011; Long et al, 2016; Starnes et al, 2020; this work). In addition, several bodies of mid‐Proterozoic orthogneiss have been mapped within the Daling‐Shumar Group (Daniel et al, 2003; Gansser, 1983; McQuarrie et al, 2019). Their contacts with metasedimentary rocks are highly strained, characterized by mylonites and ultramylonites (McQuarrie et al, 2008; our field observations).…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations